EKSISTENSI DAN OPTIMALISASI PERAN PUBLIC RELATIONS DI INDONESIA - Melita, Yerah (Istek Widuri Jakarta, 2017)
The existence of Public Relations in Indonesia in running its role is very diverse. The various roles of Public Relations in Indonesia are decided by several factors, such as factor of lack of understanding of the management of the task, function and role of Public Relations itself, the factor of position of Public Relations which is far from the top management so that in the decision of PR is not involved, and also because the position of existence of Public Relations is potluck so that it is not empowered optimally. To be able to perform its role optimally, it requires a correct understanding of the task, function and recognition of the existence of PR itself from the management or the party who has authority in an organization or company.